PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH BMT NU DENGAN KEPUASAN SEBAGAI VARIABEL MODERATING (Study Pada Nasabah BMT NU Cabang Batang Batang Kabupaten Sumenep) - Ainul Yaqin; Rois Arifin; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT His research is based on curiosity and concern for economic conditions in society. The purpose of this research is to find out and analyze whether there is an influence on the dimensions of service quality as a variable X1 and satisfaction as a moderating variable (X2) on member loyalty as a variable Y1. The results of the study then show that there is a significant effect between the dimensions of service quality on loyalty where the t test produces a significant value of 0,000 less than 0.05. Satisfaction variables significantly influence loyalty where the t test shows a significant value of 0.002 smaller than 0.05. Suggestions should be made by the Batang Batang branch of BMT NU to continuously improve the system of service quality dimensions for the sake of satisfaction that results in the creation of customer loyalty of BMT NU itself. Keywords: BMT NU Batang Batang Branch, Dimensions of Service Quality, Satisfaction, Loyalty.